Behavioral strategy : emerging perspectives - Das, T. K. (Research in behavioral strategy, 2014)
Behavioral Strategy: Emerging Perspectives contains contributions by leading scholars in the field of behavioral strategy research. The 9 chapters in this volume cover a number of significant topics that speak to the emerging perspectives in the area of behavioral strategy. The chapter topics cover both the broader issues, such as cooperative behavior in strategic decision making, cognitive orientation and biases of executives, dynamics capabilities in organizational change, and the development of metamanagement practices, and the more focused discussions on a behavioral view of business modeling, the tenets of agency theory and Austrian economics, and the temporal dimensions of strategic risk behavior. The chapters include empirical as well as conceptual treatments of the selected topics, and collectively present a wide-ranging review of the noteworthy research perspectives on behavioral strategy.